Fenomena Fear of Missing Out (FOMO) Pada Generasi Z Pengguna Media Sosial Instagram - Perdana, Dionni Ditya; Widiayanti, Widiayanti; Gushevinalti, Gushevinalti (Universitas Teuku Umar, 2024)
This study was conducted to determine the Fear Of Missing Out (FoMO) Phenomenon in Generation Z Instagram Social Media Users which aims to find out the picture of the Fear of Missing Out Phenomenon in generation Z, namely students of the Faculty of Social and Political Sciences, University of Bengkulu as active users of Instagram social media. This research uses Pierre Levy's New Media theory which discusses the development of media to analyze the phenomenon of Fear of Missing Out. The method used in this study is qualitative method, with data collection techniques through observation, interviews and documentation and informant determination through purposive sampling techniques. The results of this study show that the phenomenon of Fear of Missing Out occurs in students of the Faculty of Social and Political Sciences, University of Bengkulu towards information, news and trends on social media, especially in something they are interested in and FoMO can be seen from the fear of being left behind, worry and anxiety, dissatisfaction in themselves and anxiety that can occur in someone who is indicated FoMO. In addition, FoMO occurs due to several factors such as the tendency of internet use, intensity influenced by duration and frequency and the desire to connect with others.